Occurrence of heavy precipitation influenced by solar wind high-speed streams through vertical atmospheric coupling - Prikryl, Paul; Rušin, Vojto (Frontiers in Astronomy and Space Sciences, 2023)
A tendency of heavy rainfall-induced floods in Canada to follow arrivals of solar wind high-speed streams (HSSs) from coronal holes is observed. Precipitation events during the winter, including extreme freezing rain events in the province of New Brunswick, also tend to occur following HSSs. More direct evidence is provided using the satellite-based gridded precipitation dataset Integrated Multi-satellitE Retrievals for GPM (IMERG) in the superposed epoch analysis of high-rate precipitation. The results show an increase in the high-rate daily precipitation occurrence over Canada following arrivals of major HSSs. This is consistent with previously published results for other mid-latitude geographic regions. The ERA5 meteorological reanalysis is used to evaluate the slantwise convective available potential energy (SCAPE) that is of importance in the development of storms. The role of the solar wind-magnetosphere-ionosphere-atmosphere coupling, mediated by globally propagating aurorally excited atmospheric gravity waves releasing the conditional symmetric instability in the troposphere leading to convection and precipitation, is proposed.